Interprofessional collaboration between general practitioners and primary care nurses in Belgium: a participatory action research. - Karam, Marlène; Macq, Jean; Duchesnes, Christiane; Crismer, André; Belche, Jean-Luc (Journal of Interprofessional Care)
Given the sociodemographic challenges facing the Belgian primary care system, it is essential to strengthen interprofessional collaboration (IPC) between healthcare providers. Therefore, our aims for this study were to assess IPC between general practitioners (GPs) and nurses; identify target priorities for improving IPC; and facilitate the planning and implementation of the proposed improvement strategies. Based on diversity criteria, six groups of GPs and nurses were chosen for a participatory action research. Participants performed a SWOT analysis of their IPC to identify strengths and weaknesses of their collaboration practice configurations. Main factors limiting IPC were related to the type of financing system which impeded or facilitated multidisciplinary team meetings, a weak functional integration, and a lack of interprofessional education. Overall, communication and task delegation were co-identified as common priorities. Actions prioritized by each group were related to these two priorities and accounted for local, specific needs. Communication could be supported through improved tools and dedicating time for multidisciplinary team meetings. Task delegation was more challenging and raised questions related to nurses' training, legislation, and payment systems. IPC seems to be easier to achieve when healthcare professionals belong to the same organization and consider themselves a team.